The Use of Youtube Channel Vlog ‘Learning English with Bob the Canadian' to Increase Students’ Vocabulary Mastery - Umiwati, Riski; husnayaini, Ihda; Firdaus, Firdaus (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
This study set out to explore whether watching the English learning vlog